JEJAK WORDSWORTH, COLERIDGE, DAN SHELLEY PADA SEJUMLAH SAJAK CHAIRIL ANWAR YANG DILENGKAPI NAMA WANITA - Johan Mahyudi (Center of Language and Cultural Studies, 2015)
Almost all critiqus admit the quality of Chairicl Anwar’s verses as of impressed. On a poem he exlicitly dedicated to a certain woman he loved, Chairil Anwar impressively exposed his romantic articulation in the poet. Results of inquiry upon three poems of Chairil Anwar indicated the root of romantic initiators that derived from romantic expressions of Wordsworth, Coleridge, and Shelley. Innovations on the romantic expression the poets delivered for critiques, romantism has been a new mainstream in the literary critique. This article presents how Chairil Anwar strongly expresses romantic articulations in his three poems Cerita Buat Dien Tamaela (A Story for Dien Tamalea), Sajak Putih (A White Verse), Hampa (Empty), and Senja di Pelabuhan Kecil (Twilight in a Small Port). The findings evidently indicated that Chairil Anawar adapted Wordsworth romantism version, and Senja di Pelabuhan Kecil was a poet Chairil Anwar ideally devoted romantism spirit.